(untitled) (Hematology Meeting Reports, 2009)
Autologous stem cell transplantation (ASCT) is now recommended for young patients as part of the initial therapy or at time of the disease progression. However, almost all patients ultimately relapse and the median duration of response after ASCT does not exceed 3 years. To prolong the duration of response, maintenance therapy was a logical approach. The impact of chemotherapy as maintenance after ASCT has never been demonstrated by a randomized trial. In the eighties it was hoped that alpha interferon which prolonged remission duration after conventional chemotherapy could be even more effective in the context of HDT since the tumor burden was lower. Although the preliminary results of a small randomized study were in favour of interferon maintenance after ASCT, the differences with longer follow-up were no longer significant. The end of the story came with the results of the US Intergroup study which failed to show any difference in PFS and OS between interferon and no further treatment in 242 patients responding to either conventional chemotherapy or to ASCT.